1999
DOI: 10.1136/jech.53.11.725
|View full text |Cite
|
Sign up to set email alerts
|

Randomised studies of income supplementation: a lost opportunity to assess health outcomes

Abstract: Background-Despite the wealth of evidence linking low income to ill health, there is little information from randomised studies on how much and how quickly these risks can be reversed by improvements in income. Objective-To conduct a systematic review of randomised studies of income supplementation, with particular reference to health outcomes. Design-Extensive searches of electronic databases and contact with previous authors. As well as searching for trials that were specifically designed to assess the eVect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…Increasing uptake of welfare benefits within primary health care has been advocated as an intervention with the potential to reduce health inequalities (Acheson, 1998;Connor et al, 1999) and this approach is supported by current government policy (Department of Social Security; Secretary of State for Health Secretary of State for Scotland, Wales and Northern Ireland, 1998; Centre for Analysis of Social Exclusion, 2001). A major function entrusted to primary care trusts is responsibility for improving the health of their populations and addressing health inequalities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing uptake of welfare benefits within primary health care has been advocated as an intervention with the potential to reduce health inequalities (Acheson, 1998;Connor et al, 1999) and this approach is supported by current government policy (Department of Social Security; Secretary of State for Health Secretary of State for Scotland, Wales and Northern Ireland, 1998; Centre for Analysis of Social Exclusion, 2001). A major function entrusted to primary care trusts is responsibility for improving the health of their populations and addressing health inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Yet little research has directly evaluated the impact of increasing resources on health (Connor et al, 1999). Reviews of interventions aimed at reducing inequalities in health found few successful approaches, mostly limited to increasing uptake of preventive services or increased knowledge of healthy behaviours (Gunning-Schepers & Gepkins, 1996;Arblaster et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor mental health is consistently PROMOTING MENTAL HEALTH 204 • PROMOTING MENTAL HEALTH PROMOTING MENTAL HEALTH associated with poverty and deprivation, so it might be expected that increasing the incomes of the worst-off in society would improve mental and physical health, yet good evidence of the positive health effects of income supplementation still seems to escape us. A recent review attempted to identify all RCTs of the health outcomes of interventions such as negative income tax, housing allowances and other forms of financial assistance, including lotteries (Connor, Rogers & Priest, 1999). Only one small study -an RCT from Canada -assessed mental health outcomes following increases in income through loans and allowances.…”
Section: Overviewmentioning
confidence: 99%